PENGARUH KUALITAS PELAYANAN DAN PENANGANAN PENGADUAN TERHADAP KEPUASAN NASABAH KREDIT USAHA RAKYAT PT. BANK RAKYAT INDONESIA UNIT REJOSO SELATAN KANCA NGANJUK - Radhin Radhin; Eka Askafi (Universitas Islam Kadiri, 2019)
The purpose of this research are: (1) To know the quality of service, (2) To know the handling of complaints, (3) To know the satisfaction of customers' business credit, (4) To know the influence of service quality to customer satisfaction, 5) To know the effect of the handling of complaints on the satisfaction of business credit customers, (6) To determine the effect of service quality and handling complaints together on the satisfaction of customers' business credit. The subject of this research is customer loan business people in PT Bank Rakyat Indonesia Unit Rejoso Selatan in Nganjuk with 90 customer respondents. The method used in this research is quantitative approach. Research data obtained by questionnaire, observation, and documentation. The analysis technique used is multiple linear regression with F test and t test to test the research hypothesis. The results showed that, with the fulfillment of validity, reliability and classical assumption test, hypothesis t test proved the quality of service and handling complaints have a positive and significant impact on customer satisfaction of people's business credit. F test hypothesis proves that together, multiple regression model strengthen correlational correlation of service quality and handling of complaint to customer satisfaction of people's business credit.